(untitled) (Global Journal of Science Frontier Research, 2019)
Let us first explain what the end of stars’ lifetime means. All newly created stars are very bright. They fuse hydrogen into helium and this is the source of their light energy. However, with time as more and more hydrogen is turned into helium their brightness decreases. The middle age stars are yellow in color, like our Sun, and for them more than half of the hydrogen has been already transformed into helium. As the stars continue to age gradually they run out of hydrogen fuel. When this happen, they turn into red stars.1 When a medium size red star (up to eight solar masses) runs out of hydrogen, it starts to collapse. The contracting star now generates heat by fusing helium into carbon and oxygen.1 The next stage is fusing carbon and oxygen for energy (heat) production.1 When this happen, the contracting red stars to sustain their heat production start attracting closer and closer the nearby planets containing carbon and oxygen, peal them layer by layer, and engulf the layers for fuel. In the final stage of star evolution, the stars are white dwarfs that barely shine. Thus, observing white dwarfs and what is left from the planets orbiting them is the end of stars lifetime. The dwarf stars with carbon and oxygen cores continue to cool down for millions of years. Until recently, we didn’t know much about the white dwarfs because they barely shine and they are difficult to observe. Even more difficult is to observe the remnants of planets orbiting them.1